Establishing a Nexus between On-Street Commercial Activities, Associated Environmental Risks Hazard Risks and Planning Policy: An Exploratory Analytical Approach - B. O. Bankole; S. J. Arohunsoro; O. O. Ojo; A. A. Shittu (Archives of Current Research International, 2021)
The paper established a nexus between on-street commercial activities, associated environmental and hazard risks and environmental planning policy in Ado Ekiti. In order to achieve the objectives, a series of survey was carried out. This included site visitation, field observation, and collection of relevant data through questionnaire. A total number of 800 lock up shops were identified in various locations in the study area meant for various commercial purpose and a further 1200 slots were added for hawkers, market induced service operators, road side traders, members of Drivers’ Unions, passengers, pedestrians etc, bringing the total number to 2000 out of which 10% was sampled totaling 200 respondents in all. The two hundred respondents were randomly stratified from the Atikankan, old garage, Mathew, Irona, Ojumose, Oke-Iyinmi and Idolofin area. Out of the 200 questionnaires, only 199 were filled and returned. The study revealed that on-street commercial activities were responsible for several environmental problems and other hazards in the study area, thereby frustrating environmental planning policy. It is recommended that a more efficient rerouting of traffic along major high ways and around market locations must e adopted. Markets like Oba’s Market, Bisi Market, Erekesan Market should be developed to meet the global standard. Enough parking spaces should also be provided around these Markets to ease the commercial activities in the study area among others.